The Role Of The Head Of The School Innovator In Improving The Learning Quality Of Teachers (Case Study At Madrasah Aliyah Manbaul Ulum Tlogorejo, Karangawen, Demak) - Ainurrafiq Dawam (PT Publikasiku Academic Solution, 2024)
This article discusses the role of madrasah principals as innovators in improving the quality of teacher learning. This role includes developing teachers' professionalism, applying educational technology, and developing a relevant and up-to-date curriculum. Through the descriptive qualitative method, this study identifies various strategies used by madrasah principals in motivating and supporting teachers to improve their teaching quality. The results show that innovative madrasah principals are able to create a dynamic and collaborative learning environment, which in turn contributes to improved student achievement.